2008
DOI: 10.1016/j.drugalcdep.2007.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Transitions to regular smoking and to nicotine dependence in women using cannabis

Abstract: Background-While there is substantial support in the literature for an increased prevalence of cannabis use in cigarette smokers, emerging studies allude to the possibility that cannabis users may, in turn, be at significantly elevated risk for rapid transitions in their cigarette smoking trajectories. If there is evidence in its favor, the increased rates of cigarette smoking in cannabis users may prove to be the most significant public health problem associated with cannabis use.Methods-In a sample of 3,787 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 24 publications
4
68
0
2
Order By: Relevance
“…Knowledge about how cannabis always includes tobacco seems to be in line with the 'reverse gateway' hypothesis [10,21] according to which exposure to nicotine through cannabis consumption is a risk for nicotine dependence. Therefore, the ways of consumption, the gestures accompanying each substance, the inhalation of smoke and the presence of nicotine for both substance uses correspond and hence create a co-consumption.…”
Section: Discussionmentioning
confidence: 88%
“…Knowledge about how cannabis always includes tobacco seems to be in line with the 'reverse gateway' hypothesis [10,21] according to which exposure to nicotine through cannabis consumption is a risk for nicotine dependence. Therefore, the ways of consumption, the gestures accompanying each substance, the inhalation of smoke and the presence of nicotine for both substance uses correspond and hence create a co-consumption.…”
Section: Discussionmentioning
confidence: 88%
“…A commonfactor model -in which users progress from one drug to another because of a general susceptibility to drug dependence-could potentially explain the progression from one drug to another as different drugs become available (MacCoun, 1998(MacCoun, , 2006Morall et al, 2002;Tarter et al, 2006;Vanyukov et al, 2012). However, there is epidemiological evidence for gateway effects even when such factors are controlled (Agrawal et al, 2008;Fergusson et al, 2006), and findings with animal models support the possibility that exposure to cannabis can alter the abuserelated effects of other drugs (Cadoni et al, 2001;Ellgren et al, 2007;Panlilio et al, 2007;Solinas et al, 2004). Since there is evidence for both common-factor effects and lasting effects of drug exposure per se, and since these explanations are not mutually exclusive, it seems likely that both types of effect can occur and that they may in fact build upon each other.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, an increased risk of tobacco dependence might be the most important health consequence of cannabis use (Agrawal et al, 2008;Patton et al, 2005). Therefore, it is important to determine whether cannabis exposure per se can increase the addictive effects of nicotine.…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that young adults ages 18-25 are 10 times more likely to have ever used marijuana if they also have a history of smoking cigarettes (Lai et al, 2000). Research also documents a reverse gateway effect, whereby those who smoke marijuana in early young adulthood are more likely to initiate tobacco use and to have a greater likelihood of developing nicotine dependence than their nonsmoking peers (Agrawal et al, 2008;Behrendt et al, 2009;Okoli et al, 2008;Timberlake et al, 2007;Tullis et al, 2003). Those who go on to have problems with the use of illicit drugs, including but not limited to marijuana, are more likely to be heavy smokers, to be nicotine dependent, and to experience greater diffi culty with quitting smoking (e.g., Richter et al, 2002).…”
Section: Association Between Tobacco and Marijuana Use In Young Adultmentioning
confidence: 99%